Nursing care of an elderly patient with severe malnutrition (1例重度营养不良老年患者的护理) - YU Nana (于娜娜) (中西医结合护理)
This paper summarized the nursing interventions for an elderly patients with severe malnutrition. Nursing interventions mainly included nutrition support, multidisciplinary team care, safety protection, etc. Comprehensive and targeted nursing interventions are required to ensure the safety during hospitalization, maintain patient's body function and improve the rehabilitation of the patient. (本文总结1例重度营养不良患者的护理经验, 包括补充营养、多学科团队照护、安全防范护理等内容。护理人员通过实施全面、针对性的优质护理服务, 确保患者住院期间安全, 维护患者机体功能, 促进患者早日康复。)